2021
DOI: 10.1111/febs.16270
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour drugs targeting tau R3 VQIVYK and Cys322 prevent seeding of endogenous tau aggregates by exogenous seeds

Abstract: Emerging experimental evidence suggests tau pathology spreads between neuroanatomically connected brain regions in a prion-like manner in Alzheimer's disease (AD). Tau seeding, the ability of prion-like tau to recruit and misfold na€ ıve tau to generate new seeds, is detected early in human AD brains before the development of major tau pathology. Many antitumour drugs have been reported to confer protection against neurodegeneration, supporting the repurposing of approved and experimental or investigational on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
(105 reference statements)
1
3
0
Order By: Relevance
“…We found in our earlier study that intracellular seeding in cells induced with R3 fibrils corresponds to reduced cell growth [31]. In this study, we observed the decreased proliferation of R2 and R3-induced cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found in our earlier study that intracellular seeding in cells induced with R3 fibrils corresponds to reduced cell growth [31]. In this study, we observed the decreased proliferation of R2 and R3-induced cells.…”
Section: Discussionsupporting
confidence: 70%
“…[30]. We previously reported a reduction in the growth of cells induced with R3 fibrils [31]. Therefore, we examined phospho-Histone H3 (Ser10) levels in the cell population sorted based on 0, 50 and 100% intracellular aggregate positivity (Ag+) after induction with R2 and R3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, it has been reported that many VQIVYK inhibitors can block the heparin-induced assembly of full-length Tau [60][61][62]. Recently, the Das' team reported by AFM analysis that 10 µM QCT abrogated R3 peptide fibrillation [63]. More interestingly, the authors demonstrated that QCT was able to prevent seeding of endogenous Tau aggregates by exogenous seeds.…”
Section: Discussionmentioning
confidence: 98%
“…319 Similarly, we recently showed that drugs like paclitaxel, doxorubicin, resveratrol, and quercetin that interact with the amyloid motif and cysteine residue in tau repeat 3 block its nucleation-dependent aggregation, abolishing the formation of toxic, pathological prion-like aggregates of tau. 321 The concept of removal of a toxic burden of misfolded proteins is not new. Sequestering oligomers from human patients with tau-positive inclusions in brains is expected to abolish tau spreading, even after pathological tau deposition has begun.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%